Comparison between the Outcome of Tunica Vaginalis Blanket Wrap and Non-wrap Procedures in Urethroplasty (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Hypospadias is a developmental anomaly characterized by a urethral meatus that opens onto the ventral surface of the penis, proximal to the end of glans. Fistulas are the most common complication following hypospadias repairs. This study was carried out to see that application of vascularized Tunica Vaginalis Blanket Wrap (TVBW) in urethroplasty reduces fistula rate in hypospadias repair. Objectives: To study the efficacy of Tunica vaginalis blanket wrap to prevent urethrocutaneous (UC) fistula in urethroplasty for hypospadias repair.Methods:Study Design : Prospective comparative studyPlace of Study :Department of Paediatric surgery, Dhaka Shishu Hospital (DSH), Dhaka.Period of Study :April, 2003 to October, 2004 for a total period of 19 months.The study of population : Twenty (20) admitted patients of hypospadias were selected. Patients were grouped into group A and group B on the basis of lottery method. Group A included 10 cases, who were subjected to repair of hypospadias with the application TVBW. Group B included 10 cases, who were subjected to repair of hypospadias without TVBW.Statistical Analysis : Chi-square test (X2 test) were applied. p value